1996
DOI: 10.1142/s0218127496001594
|View full text |Cite
|
Sign up to set email alerts
|

Lorenz Equation and Chua’s Equation

Abstract: The dynamical properties of two classical paradigms for chaotic behavior are reviewed—the Lorenz and Chua’s Equations—on a comparative basis. In terms of the mathematical structure, the Lorenz Equation is more complicated than Chua’s Equation because it requires two nonlinear functions of two variables, whereas Chua’s Equation requires only one nonlinear function of one variable. It is shown that most standard routes to cbaos and dynamical phenomena previously observed from the Lorenz Equation can be produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The existence of closed curves of global bifurcations (homoclinic and heteroclinic connections) in Chua's equation [28] has been reported numerically [4]. The mechanism of formation/destruction on such curves, when a third parameter is moved, is also qualitatively described and is related to a failure of transversality of a curve of T-points in a three-dimensional parameter space.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The existence of closed curves of global bifurcations (homoclinic and heteroclinic connections) in Chua's equation [28] has been reported numerically [4]. The mechanism of formation/destruction on such curves, when a third parameter is moved, is also qualitatively described and is related to a failure of transversality of a curve of T-points in a three-dimensional parameter space.…”
Section: Introductionmentioning
confidence: 92%
“…If we substitute the value of z given by equation (17) into (30), after some tedious algebra, it is possible to obtain an equivalent system, up to first order, to (27)- (28). This system is written in the following theorem:…”
Section: Cusp Bifurcationsmentioning
confidence: 99%
“…The Chua oscillator The Chua circuit is described by the following state equations ( [Pivka et al, 1996]):ẋ…”
Section: The Rössler Oscillatormentioning
confidence: 99%
“…More precisely, in the next section we study pairs of coupled chaotic oscillators, but for three different types of oscillators, namely Lorenz system ( [Lorenz, 1963]), Rössler oscillator ( [Rössler, 1976]), and Chua circuit ( [Pivka et al, 1996]). Of course the analysis is performed by varying local coherence and coupling strength and by fixing parameter values which guarantee that these oscillators produce low-dimensional chaos when they are uncoupled.…”
Section: Introductionmentioning
confidence: 99%
“…The study of circuits with polynomial non-linearity, especially of electronic chaos oscillators such as Chua's circuit, has been a topic of increasing interest for some time [1][2][3][4]. It was reported that not all features of a real circuit with a smooth non-linearity were correctly captured by the circuit with a piecewise-linear approximation.…”
Section: Introductionmentioning
confidence: 99%